ANALISIS ANGGGARAN BIAYA PRODUKSI PADA PERUSAHAAN MANUFAKTURE - Sulaeman, Risaldi; Uchlis, Chofiuddin (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study is to find out how big the role of production costs in the company and how to control production costs at the Trend Furniture furniture company. Variables used in this study Control of production costs (X). The method used in this research is descriptive research method with a qualitative approach. The social situation in this research is Place: Furniture Trend. Actors: Owner, Management, and Treasurer. Activities: Observations, and interviews in 2020 with primary and secondary data collection techniques. Based on the results of the research that has been done, it can be seen that there is a difference in the planning of the production cost budget with its realization at the Trend Furniture furniture company where the total production cost budget reaches Rp. 1,703,210,500 meanwhile the total realization of production costs reached Rp. 2,663,912,500 so there is a difference of 56% while the standard difference in production costs set by the company only reaches 10%, it means the difference in 2020 exceeds the standard difference in the company.